PREVISÕES TRADICIONAIS DE TEMPO E CLIMA NO CEARÁ: O CONHECIMENTO POPULAR À SERVIÇO DA CIÊNCIA / Traditional weather and climate forecasts in Ceará: lay knowledge in the service of science - Nelson Donald; Marcelo Theophilo Folhes (Sociedade & Natureza)
This article examines the meteorological interpretations of phenomenon that are made bycareful observers of nature. The climate forecasts, made by the sertanejos and based onempirical observations, have relevance for the probability-based climate forecasts developedby meteorological institutions. In 1998 research was carried out in six different municípiosand microclimates during the months of January and February. A total of 484 householdinterviews were conducted. One research objective was to better understand the lay methodsinvolved in developing weather and climate forecasts. Both the lay forecasts as well as theinstitutional forecasts are incomplete and constantly improving. Increasing our understandingof how empirically based forecasts are used by the sertanejos is one way to influence the acceptance of other methods of predicting climatic conditions.Keywords: